Nupe Religion - Nadel, S. F. (Routledge, 1954)
Originally published in 1954, this book is a pentrating study of Nupe religion and the increasing influence that Islam has had on indigenous forms of worship. The practise of witchcraft, forms of ritual, Gods and faith in medicine are all examined as an integral part of Nupe religion and culture.
free